The impacts of internet and transportation access on patients’ health conditions: a cross-sectional study - Hu, Qinglin; Li, Xiaobing; Bell, Gregg; Yerby, Lea G. (International Journal Of Community Medicine And Public Health, 2022)
Background: Use of internet and transportation to access to healthcare resources are 2 essential and effective ways to promote health outcomes and ameliorate health disparities. Despite general widespread availability of internet and transportation, disparities still exist among specific groups and regions. Little is known about the spatial patterns of extents of 2 access determinants on healthcare resources, nor for their compound effects on patient’s health outcomes. Methods: The study uses 2018 health information national trends survey (HINTS) data, geographic information techniques and multiple ordered logistic regression model were applied. Results: The results show that States in West and Midwest tend to have higher proportions on both perspectives, where states in South and Mideast had a relatively low percentage on the healthcare access determinants. Those states had similar socio-economic patterns with underserved population and low development progress in public healthcare system. Another finding is urban people had outstripped its rural neighbors on both internet (79% vs 57%) and transport (74% vs 62%) access to healthcare resources. Furthermore, our study suggests that, when considering compound effects of internet access for healthcare information and transport access to healthcare service, people who had greater barriers tend to have decreased likelihood (-21.30%) towards their health conditions, compare to those with sufficient accesses. Conclusions: Additional work and policy are needed to ensure that internet and public transportation resources and services are prioritized for underserved populations and areas.